Correlation between orthodontic treatment and temporomandibular joint disorders: Hubungan antara perawatan ortodonti dengan gangguan temporomandibular joint - Eddy Heriyanto Habar; Clarisa Batara Dase (Makassar Dental Journal PDGI Makassar, 2023)
Orthodontic treatment aims to regulate the growth and development of the jaw and teeth. The temporomandibular joint (TMJ) is a hinge joint that connects the upper and lower jaw bones between the temporal bone and the head of the mandibular con-dyle. Orthodontic treatment of patients with a history of restriction of TMJ movement experienced statistically significant re-sults and reduction of TMJ pain. The results of the analysis of 6 journals stated that orthodontic treatment had a significant re-lationship with temporomandibular joint disorders. Orthodontic treatment can cause TMD such as structural disorders of the TMJ and functional disorders. Orthodontic treatment can also help overcome TMD such as reducing pain in the TMJ and pro-viding balance to the occlusion.